Oral hygiene awareness and practices among a sample of primary school children in Rural Bangladesh - Bhuiyan, Md. Al-Amin; Binte Anwar, Humayra; Binte Anwar, Rezwana; Ali, Mir Nowazesh; Agrawal, Priyanka (MDPI, 2022)
This article was published in Dentistry Journal by MDPI [ This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited] and the definite version is available at: https://doi.org/10.3390/dj8020036 The Journal's website is at: https://www.mdpi.com/2304-6767/8/2/36